2021
DOI: 10.1016/j.esmoop.2021.100168
|View full text |Cite
|
Sign up to set email alerts
|

Primary tumor side is associated with prognosis of colorectal cancer patients with brain metastases

Abstract: Background Brain metastases (BM) are a rare complication in colorectal cancer (CRC) patients and associated with an unfavorable survival prognosis. Primary tumor side (PTS) was shown to act as a prognostic and predictive biomarker in several trials including metastatic CRC (mCRC) patients. Here, we aim to investigate whether PTS is also associated with the outcome of CRC patients with BM. Methods Patients treated for CRC BM between 1988 and 2017 at an academic care cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…In a univariate analysis, Huerta et al [ 43 ] found that patients with RCC had a poorer survival rate than those with LCC (4.6 vs. 10.7 months; HR 3.5, p = 0.025), but in a multivariate Cox regression analysis, the difference was not significant. Another study found that CRC BMs patients with a left-sided primary tumor had a 1.5-fold better prognosis than those with a right-sided primary [ 14 ]. Right-sided CRC has a poorer prognosis than left-sided CRC, as evidenced by a greater prevalence of mucinous, undifferentiated, and signet-ring cell tumors, as well as a later stage of cancer at diagnosis [ 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a univariate analysis, Huerta et al [ 43 ] found that patients with RCC had a poorer survival rate than those with LCC (4.6 vs. 10.7 months; HR 3.5, p = 0.025), but in a multivariate Cox regression analysis, the difference was not significant. Another study found that CRC BMs patients with a left-sided primary tumor had a 1.5-fold better prognosis than those with a right-sided primary [ 14 ]. Right-sided CRC has a poorer prognosis than left-sided CRC, as evidenced by a greater prevalence of mucinous, undifferentiated, and signet-ring cell tumors, as well as a later stage of cancer at diagnosis [ 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of CRC BMs is also affected by the location of the underlying tumor. Compared to patients with left-sided CRC, those with right-sided CRC develop BMs much earlier and have a significantly worse prognosis [ 14 ]. The treatment of metastatic CRC has altered substantially in recent years, owing mostly to the development of targeted treatments and immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Even in recent reports, the prognosis of patients harboring CRC BMs generally remains dismal, with a median survival of 5-10 months [ 2 - 6 ]. In addition, right-sided CRC (including the appendix, cecum, and ascending colon) is associated with an unfavorable prognosis, compared with left-sided CRC (including the descending colon, sigmoid, and rectum) [ 7 ]. BMs from cecal cancer without any other simultaneous, distant metastases are extremely rare in either a synchronous or metachronous setting [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies have revealed the genetic heterogenicity of colorectal cancers, as evidenced by concurrent high-and lowfrequency mutations and transcription profile drift (10, [14][15][16]). These factors affect the susceptibility of colorectal cancer to pharmaceutical chemicals and prognosis of the patients (12,(17)(18)(19)(20). With respect to anatomical heterogeneity, the right-sided intestine originates from embryonic midgut, while the leftsided large intestine originates from embryonic hindgut.…”
Section: Introductionmentioning
confidence: 99%